Effect of Planting Space and Dose of Phosphate Fertilizer on the Development and Production of White Sorghum (Sorghum bicolor L. Moench) Samurai-2 Variety - Amran Jaenudin; Dukat Dukat; Utyta Alaydrus; Maryuliyanna Maryuliyanna (The University of Lampung, 2023)
White sorghum is utilized for food, beverage, fodder, and other industrial purposes. Spacing and fertilization are among problems for the development of sorghum plants. The aim of this study was to evaluate the interaction effect of planting space and phosphate fertilizer treatments on the development and production of white sorghum (Sorghum bicolor L. Moench) varity of Samurai-2, and to determine the best results from those treatments as well. This research was performed at the experimental field of Al-Zaitun Islamic Boarding School located in Mekarjaya Village, Subdistrict of Gantar, Indramayu Regency, West Java. A factorial randomized block design was employed with planting space treatment of PS30 (70 cm × 30 cm), PS40 (70 cm × 40 cm), and PS50 (70 cm × 50 cm) and phosphate fertilizer treatment of PF50 (50 kg/ha), PF100 (100 kg/ha), and PF150 (150 kg/ha). Response parameters consisted of plant heigh, number of leaves, leaf area index (LAI), stem diameter, root volume, plant growth rate, and crop yield (weight of 1000 grains and yield per plot). Results of this study showed no interaction in all treatments, and the PS30 with crop spacing of 70 cm x 30 cm resulted the best yield on weight per plot of 5.08 kg/plot equivalent to 8.5 ton/ha. Keywords : Crop yield, Growth rate, Leaf area index, Plant height, Stem diameter